Rollover risk, liquidity, and macro-prudential regulation - Toni Ahnert (European Central Bank (ECB), 2014)
I study rollover risk in the wholesale funding market when intermediaries can hold liquidity ex-ante and are subject to fire sales ex-post. I demonstrate that precautionary liquidity restores multiple equilibria in a global rollover game. An intermediate liquidity level supports both the usual run equilibrium and an efficient equilibrium. I provide a uniqueness refinement to characterize the privately optimal liquidity choice. Because of fire sales, liquidity holdings are strategic substitutes. Intermediaries free-ride on the liquidity of other intermediaries, causing excessive liquidation. A macro-prudential authority internalizes the systemic nature of liquidity and restores constrained efficiency by imposing a macro-prudential liquidity buffer.
Keywords: G01; G11; G28; 330; global games; multiplicity; portfolio choice; wholesale funding